Cardiac involvement in a patient with B-cell lymphoblastic lymphoma/acute lymphoblastic leukemia and a history of allogeneic hematopoietic stem cell transplantation and CAR T-cell therapy: A case report - Cao, Yigeng; Liu, Yadan; Zhang, Rongli; Zhai, Weihua; Ma, Qiaoling; Wei, Jialin; Yang, Donglin; Pang, Aiming; He, Yi; Chen, Xin; Jiang, Erlie; Feng, Sizhou; et al. (Frontiers in Immunology, 2023)
Cardiac involvement is uncommon in hematologic malignancies and often leading to poor prognosis. Furthermore, only a few cases had been reported. In this manuscript, we reported a 42-year-old woman with a history of allogeneic hematopoietic stem cell transplant (allo-HSCT) and chimeric antigen receptor t (CAR-T) cell therapy for B cell lymphoblastic lymphoma (B-LBL)/acute lymphoblastic leukemia (B-ALL) developed cardiac mass and myocardial infiltration. Prior to this presentation, massive pericardial effusion occurred half a year after CAR-T treatment, which was improved by ultrasound-guided pericardiocentesis. In these two cardiac-related clinical symptoms, we found elevated cytokines and copy of CAR DNA whether in pericardial effusion or serum. She received Tocilizumab (humanized monoclonal antibody against IL-6 receptor) controlling serum cytokines and a reduced-intensity chemotherapy with vindesine, cyclophosphamide and prednisolone (VCP) after developing cardiac mass and myocardial infiltration. However, she finally died of multiple organ failure (MOF). This is the first report about cardiac mass and myocardial infiltration after allo-HSCT and CAR-T cell therapy, which may provide supporting data for early diagnosis and immediate treatment of patients with cardiac involvement.